The Politics of Leisure Policy / Public Policy and Politics - Henry Ian P; Macmillan (1993)
A systematic account of the impact of social, economic and cultural change on demand for leisure and of the response of politicians, professionals and service providers. Preface, The Politics of Leisure and Policy, Political Ideology and Central Government Leisure Policy, Leisure and the State and Policy in Modern Britain, Local Government and Leisure Policy: The Heritage of Thatcherism, The Leisure Professionals, The Commercial and Voluntary Sectors, Leisure Policy and Post-Fordism and Local Government, Guide to Further Reading, References, Index.